Skinfold Anthropometry -The Accurate Method for Fat Free Mass Measurement in COPD - Hronek, Miloslav; Kovarik, Miroslav; Aimova, Petra; Koblizek, Vladimir; Pavlikova, Ladislava; Salajka, Frantisek; Zadak, Zdenek (Chronic obstructive pulmonary disease, 2013)
AbstractPurpose: Fat free mass index (FFMI) is an independent predictor of metabolic and functional consequences in COPD. For its measurement dual energy X-ray absorptiometry (DEXA), skin-fold anthropometry (SFA), bioelectrical impedance analysis (BIA) and bioimpedance spectroscopy (BIS) are used in clinical practice. The aim of our pilot study was to analyse precisely and critically which method is most accurate and available for common use in clinical practice for measurement of FFM by assessment against relevant DEXA in patients with COPD. Methods: This was an observational cross-sectional study of consecutive COPD subjects. FFM by methods of SFA, two versions of BIA, and BIS was compared with that from clinically relevant DEXA in 41 outpatients (mean age 66.5 ± 7.7 yrs) with stable COPD, 34 men and 7 women, with mean BMI 28.2 ± 6.1 kg.m−2. Results: All methods underestimate FFM in comparison with DEXA. In the general evaluation non-significant differences with the smallest mean bias were demonstrated for SFA (1.2 kg) and BIA (3.8 kg), but there was a difference of more than 9 kg using BIS and BIA COPD methods (p < 0.0001). The best agreement between DEXA and SFA was demonstrated via Lin's concordance coefficient and Bland-Altman test. Conclusions: SFA has been demonstrated as an accurate, available and cheap method for determination of FFM and FM with application of the Durnin Womersley equation for body density and with the Siri equation for FM in patients with COPD. SFA can be easily applied in routine clinical practice.